Morphing restrictive gender roles into performative gender roles in Chimamanda Ngozi Adichie’s hibiscus pourpre (2021)
Through feminist literature and other forms of feminist endeavours to institutionalise gender equality, the notion of biology is destiny as identified by the social and natural sciences has come under the attack of feminists. Debunking the stereotyping of women and assignation and restriction of specific gender roles to specific sex whereby certain roles are christened as women’s roles and certain others as men’s roles is part of this feminist project. In Hibiscus Poupre, Chimamanda Adichie weaves in the flexibility of roles to engage with the theme of gender roles and performativity. From what she demonstrates, the fixity of gender roles through decades of cultural construction can be deconstructed and reconstructed to foster harmony among the genders. Womanism as a theory that focuses on complementarity of gender roles is used to interrogate and x-ray the subtle ways in which the author downplays gender role stereotyping and brings to the fore the pivotal roles of African Women using Igbo ethos construct as model. Under the pretext of being a practising Catholic, Eugene, Tatie Ifeoma’s biological brother, neglects the care of his aged father whom he accuses of idolatry. He thus jettisons the traditional roles expected of a male child in Igbo society. The female, Tatie Ifeoma is seen laden with the responsibilities that the male child fails to carry out traditionally. Within her household, chores are shared between male and female children without pigeonholing of roles. Every member of the family diligently carries out their responsibilities without reference to whether a particular chore is meant for female or male. This is seen to be one of the core factors for harmony in Tatie Ifeoma’s household where the latter, a widow and poorly paid faculty at the University of Nsukka, plays the family head. In conclusion, emphasises that gender performativity is not typecast. The author demonstrates how Western religion is used to obliterate and suppress traditional African religions and their practitioners. Gender role iteration is also allowed in reversed order to deconstruct conventional tradition of allocating roles based on gender.